Adsorption characteristics of Pb2+ and Zn2+ from simulated acid mine drainage using lees - DONG Ying-bo; LIN Hai; HE Yin-hai; LIU Quan-li (工程科学学报)
In order to study the ability of lees to adsorb heavy metals,this article was focused on the effects of wastewater p H values,Pb2+ and Zn2+ mass concentrations,and adsorption time on the adsorption quantity of Pb2+ and Zn2+ from simulated acid mine drainage using lees. Test results show that the maximum removal rate appears when the p H value is 4. The adsorption of Pb2+ by lees accords with the Langmuir equation,but the adsorption of Zn2+ is followed by the Freundlich equation. Under the optimal conditions,the maximum adsorption capacity of Pb2+ and Zn2+ by lees is 8.29 mg·g-1 and 15.31 mg·g-1,respectively. The adsorption process reaches equilibrium after 4 h,in agreement with the second-order kinetics model. The contents of cellulose,hemicelluloses and lignine in the lees is 23.3%,65.5% and 0.5%,while become 19.6%,42.3% and 2.6% after adsorption of Pb2+ and Zn2+,respectively. The electro-negativity of lees increases while the p H value raises,and it reduces after adsorption of Pb2+ and Zn2+. Fourier transform infrared spectra indicate that the main functional groups are amide and ester reacting in the adsorption process.